2018
DOI: 10.1007/s00134-018-5433-0
|View full text |Cite
|
Sign up to set email alerts
|

Restricted fluid resuscitation in suspected sepsis associated hypotension (REFRESH): a pilot randomised controlled trial

Abstract: To determine if a regimen of restricted fluids and early vasopressor compared to usual care is feasible for initial resuscitation of hypotension due to suspected sepsis. Methods: A prospective, randomised, open-label, clinical trial of a restricted fluid resuscitation regimen in the first 6 h among patients in the emergency department (ED) with suspected sepsis and a systolic blood pressure under 100 mmHg, after minimum 1000 ml of IV fluid. Primary outcome was total fluid administered within 6 h post randomisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(137 citation statements)
references
References 31 publications
5
124
0
Order By: Relevance
“…17 Our study found that the restricted fluid and early vasopressor regimen resulted in a significantly lower volume of fluid administered over the first 24 h of care, with no signal of harm. 17 Our study found that the restricted fluid and early vasopressor regimen resulted in a significantly lower volume of fluid administered over the first 24 h of care, with no signal of harm.…”
Section: Introductionmentioning
confidence: 53%
“…17 Our study found that the restricted fluid and early vasopressor regimen resulted in a significantly lower volume of fluid administered over the first 24 h of care, with no signal of harm. 17 Our study found that the restricted fluid and early vasopressor regimen resulted in a significantly lower volume of fluid administered over the first 24 h of care, with no signal of harm.…”
Section: Introductionmentioning
confidence: 53%
“…Although one of the studies that emphasized earlier restrictions of volume reported an earlier time to the use of vasopressors in the restrictive group, no difference was observed in overall vasopressor use in this study or across any of the other studies (Table ). No significant increase in vasopressor‐associated limb ischemia was observed across the four studies that reported this outcome .…”
Section: Dosing Of Fluids In Sepsis During the Initial Resuscitation mentioning
confidence: 80%
“…Beyond the studies conducted in resource-limited settings, five additional studies [37][38][39][40][41] in 497patients examined either a restrictive or a conservative (usual care) fluid approach in septic patients for a total of 706 patients across the six studies ( Table 2). Three of these studies 37,40,41 (293 subjects) examined a restrictive approach after 25-30 ml/kg of fluids had already been administered during EGDT.…”
Section: Restrictive Resuscitation Meta-analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations